The Nation State A Wrong Model for the Horn of Africa - Markakis, John (Max Planck Research Library for the History and Development of Knowledge: Studies, 2021)
This book analyses recent political developments in the Horn of Africa in light of actual identifications and alliances. The nation state-the normative framework for politics-is often shown as a non-relevant unit of identification and beneficiary of political decisions. The authors have spent their professional lifetimes studying the politics and development in Sub-Saharan Africa since its emergence from colonial rule. The Horn of Africa, their special focus of interest, represents a striking paradigm of the enduring crisis of the western nation-state model adopted in Africa. Questions concerning this model have seldom been raised in African studies. A notable exception is Basil Davidson (1992) who called the nation-state model the "Black Man's Burden." Francophone Africanists were pioneers in economic anthropology and prolific critics of orthodox development theory but had little to say about the state which they regarded as a dependent variable. This omission therefore challenges the epistemological integrity of African studies. Where is the science this discipline is based on? Founded in the West and dominated by western scholars, African studies thrive on modes of analysis that privilege European categories, or ascribe greater rationality and capacity for agency to Western rather than all other historical actors. This book explores this logic and shows that the decisions made by these actors are determined by identifications and interests that have little to do with the nation state.